2006
DOI: 10.1007/s11427-006-0201-8
|View full text |Cite
|
Sign up to set email alerts
|

Genetic regulation by non-coding RNAs

Abstract: Large scale cDNA sequencing and genome tiling array studies have shown that around 50% of genomic DNA in humans is transcribed, of which 2% is translated into proteins and the remaining 98% is non-coding RNAs (ncRNAs). There is mounting evidence that these ncRNAs play critical roles in regulating DNA structure, RNA expression, protein translation and protein functions through multiple genetic mechanisms, and thus affect normal development of organisms at all levels. Today, we know very little about the regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 159 publications
0
6
0
Order By: Relevance
“…Southern Australian rainfall is influenced by a large number of weather systems including extratropical and subtropical cyclones, low pressure troughs, thunderstorms, cold and warm fronts, and transient and blocking high pressure systems (Sturman and Tapper 1996). Several previous studies have investigated the contribution of these weather systems individually to Australian rainfall as well as how they may have changed over recent decades, including for low pressure systems (Pepler et al 2014a;Lavender and Abbs 2013;Ng et al 2015;Qi et al 2006), high pressure systems (Pepler et al 2019b), and northwest cloud bands (Reid et al 2019). In addition, there have been several studies that attempt to attribute all rainfall in a given region to a larger number of synoptic types using either manual classification or selforganising maps, including Victoria in southeast Australia (Wright 1989;Risbey et al 2013;Verdon-Kidd and Kiem 2009), southwestern Western Australia (Pook et al 2011), and tropical Australia (Moron et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Southern Australian rainfall is influenced by a large number of weather systems including extratropical and subtropical cyclones, low pressure troughs, thunderstorms, cold and warm fronts, and transient and blocking high pressure systems (Sturman and Tapper 1996). Several previous studies have investigated the contribution of these weather systems individually to Australian rainfall as well as how they may have changed over recent decades, including for low pressure systems (Pepler et al 2014a;Lavender and Abbs 2013;Ng et al 2015;Qi et al 2006), high pressure systems (Pepler et al 2019b), and northwest cloud bands (Reid et al 2019). In addition, there have been several studies that attempt to attribute all rainfall in a given region to a larger number of synoptic types using either manual classification or selforganising maps, including Victoria in southeast Australia (Wright 1989;Risbey et al 2013;Verdon-Kidd and Kiem 2009), southwestern Western Australia (Pook et al 2011), and tropical Australia (Moron et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In total, 2327 lncRNAs were obtained after assessing the protein-coding potential of coexpressed mRNAs based on the two software programs, CNCI and CPC (Figure 1A), with 607 genes aligned against the known lncRNAs from the TAIR database of model plant Arabidopsis (Figure 1B), and 345 lncRNAs with coexpressed mRNAs of A. sinensis identified (Figure 1C) based on the SwissProt database. Based on the biological functions, the 272 characterized lncRNAs (Figure 1D) were divided into six categories: chromatin, DNA/RNA and protein modification (29); flowering (36); stress response (24); metabolism (117); biosignaling (23), and energy and transport (43) (Figure 1E). The base sequences of the 272 lncRNAs are shown in Table S2.…”
Section: Lncrnas Analysismentioning
confidence: 99%
“…It is now evident [246][247][248][249][250] that nonprotein coding RNA (ncRNA) plays a critical role in regulating the timing and rate of protein translation.…”
Section: Regulatory Rnamentioning
confidence: 99%
“…Large scale cDNA sequencing and genome tiling array studies have shown [248] that around 50% of genomic DNA in humans is transcribed, of which 2% is translated into proteins and the remaining 98% is non-coding RNAs (ncRNAs). Today, we know very little about the regulatory mechanisms and functions of these ncRNAs.…”
Section: Regulatory Rnamentioning
confidence: 99%